An exploratory study on the critical thinking skills and processes manifested in the reading logs of selected freshman students of De La Salle University-Manila - Tan, Neslie Carol C. (Animo Repository, 2011)
In 1984, bell hooks came up with the book entitled Feminist theory: from margin to center, this work rocked the feminist status quo by critiquing the work of modern feminists who happened to be all white, privileged women. Hooks insisted that reformist feminism did not address the plight of other women, those who were oppressed not only by the factor of sex alone, but by other factors such as race and class. Hooks proposed a new radical feminism which took into consideration the intricate web of oppressive factors enacted by the dominating system in place, referred to as white capitalist supremacist patriarchy. Since feminist theory is all about eradicating oppression in all fronts, hooks's contribution goes beyond forwarding a theory of feminism by proposing a way to awaken the consciousness of the masses through the process and practice of cultural criticism. Hooks' cultural criticism theory is highly influenced by her feminist theory. Her starting point is the black, working class experience. She invites critics and everyday people to examine common representations and images through a series of interrogation techniques. These representations are motivated and reinforce systems of domination. The challenge posed for feminists is to eradicate oppression by raising critical awareness, influencing enlightened witnesses and transforming culture. The problem with her cultural criticism, though, is that it is virtually unknown in the philosophy canon. Furthermore, it has also been labeled as essentialist and her methods allegedly lack consistency. This study critically evaluates hooks method of cultural criticism using a postfeminist lens. Postfeminism is feminisms turn to culture it is the meeting point of postcolonial feminism, cultural/media studies and postmodernism. Postfeminism recognizes pop culture as a site of struggle and tries to find a common solution to women's oppression despite women's diversities. Through a review of her feminist theory, a constructive critical assessment of her cultural criticism, alongside other contemporary postfeminists, I find out how hooks fares as a pop culture critic. How does she provide a unifying solution for the decolonization and liberation of women through her pop culture criticism? At the same time, how can I reimagine her as a postfeminist pop culture critic despite issues and contradictions in her theory and methods? Some of the contradictions in hooks’ theory include too much focus on black experience rather than other women’s experiences, an alleged failure to include a global perspective and an exclusive method of critique. Although hooks fails to explicitly define a method of critique, she consistently applies a process that 1) uses a pluralistic lens to recognize the absence of oppressed groups, 2) an inquiry into how oppressed/oppressors’ groups are represented, and finally, 3) an analysis of the impact of the images on certain groups. hooks’ theory itself is a solid postfeminist framework for pop culture critique with the following recommendations: a clarification of her definition of blackness and whiteness, an emphasis on her theory of crossing the borders and her self-interrogation process, a focus on feminist solidarity as a commonality of feeling and a global transgression of boundaries in her critique of representations. In order to enrich hooks’ call for a critical consciousness, her cultural criticism theory must make the shift from radical voice to a global voice, from selfinterrogation to a mutual interaction, and from feminist diversity to feminist solidarity. Consequently, this may lead to a critical awakening of a postfeminist consciousness -a movement from silence to speech, from margin to center, from oppression to freedom.